以情境式試題評量中學生能源素養 Using Contextualized Assessment to Measure - 陳冠利 Kuan-Li Chen; 劉湘瑤 Shiang-Yao Liu; 陳柏熹 Po-Hsi Che; 黃書涵 Su-Han Huang (National Taiwan Normal University, 2015)
能源素養為知識、態度與行為組成的多面向架構，為瞭解學生能源素養的表現情形，本研究以先前發展的能源素養架構為基礎，對應各指標內涵設計六個情境式題組作為評量工具，以全國國、高中學生為施測對象，共取得2,066份有效樣本。結果顯示，學生的能源素養尚需加強，尤其是評估與判斷國際能源議題的素養指標能力，另從評量試題的文字作答分析發現，學生對溫室效應成因和生質能源等議題持有迷思概念。相關分析呈現知識與行為面向的關聯性較態度與行為的關聯性高。對節能減碳的看法和參加研習次數與素養表現有正相關；年級愈高的學生在素養的整體表現上愈好。本研究建議發展有效的能源課程及教學方式，作為能源教育推動策略之參考。 Energy literacy is multidimensional, comprising broad content knowledge as well as affect and behavior. In this study, an assessment was designed using six contextualized test units to examine student energy literacy. A total of 2,066 secondary students participated in the survey. The results indicated that student energy literacy is low, particularly with respect to the dimension of "reasoning on energy controversies". Qualitative analyses of student written responses to various question items revealed that students have misconceptions of biomass energy and misconstrue the sources of greenhouse gas. Inter-correlation among the dimensions of energy literacy indicated that energy knowledge and behavior are more closely correlated with each other than are affect and behavior. The students in southern Taiwan scored higher on energy literacy assessments than did the students in northern, central, as well as eastern Taiwan. These findings are a reference for developing energy-related curricula and educational materials to improve student energy literacy.